Terrorism in the World: Mistakes in Understanding the Role of Religion - Dea Amelia; Hisny Fajrussalam; Jihan Fauziah; Zulfa Syarifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Terrorism is often a major threat to a nation. Terrorism movements are motivated by psychological, economic, cultural, political, and religious problems of a group. This is a complex issue. However, it becomes more sensitive when religious motivations are involved. Nevertheless, terrorism is a humanitarian problem that urges all people and state and religious institutions to find a solution. Then what is the role of religion in providing correct understanding and actualizing its role in overcoming the problem of terrorism? How do people, especially Muslims, understand the message of religion? Overcoming the problem of terrorism is the first step to building a peaceful social life. The next step is to advance humanity. After all, the state and religion have the same responsibility in educating all people to live universal values such as brotherhood, peace, justice, and mutual respect and help as a way of life.